Python for Offensive PenTest a practical guide to ethical hacking and penetration testing using Python. - Khrais, Hussam (Packt Publishing, 2018)
Python is an easy-to-learn and cross-platform programming language which has unlimited third-party libraries. Plenty of open source hacking tools are written in Python and can be easily integrated within your script. This book is divided into clear bite-size chunks so you can learn at your own pace and focus on the areas of most interest to ...